Isoxys (Arthropoda) with preserved soft anatomy from the Sirius Passet Lagerstatte, lower Cambrian of North Greenland - Stein, M; Peel, J; Siveter, D; Williams, M (2010)
Isoxys volucris is the most commonly occurring species in the lower Cambrian Sirius Passet Lagerstätte of North Greenland. Newly identified material allows a first, limited, account of the ventral morphology of this species, hitherto known only by the morphology of its shield. The antennula is large and robust, composed of about seven articles armed with spines, and was probably not sensorial. The postantennular limbs are serially similar, biramous with a large paddle-shaped exopod fringed with setae. It is possible that the animal possessed a furca. The inner lamella, lining the ventral surface of the shield is recognised in Isoxys for the first time. Comparisons with other congeneric species of which aspects of the ventral morphology are known, show similarities with Isoxys auritus from China, reconsidered here, but indicate differences in antennular morphology with other species as currently understood. □ Cambrian, Greenland, Isoxys, soft anatomy, Sirius Passet, palaeoecology. © 2009 The Authors, Journal compilation © 2009 The Lethaia Foundation.